Working time flexibility and work-life balance - Anne M. Wöhrmann; Nicola Dilchert; Alexandra Michel (Zeitschrift für Arbeitswissenschaft, 2020)
Based on border theory (Clark 2000), we aim to investigate the relationship between individual-oriented and organization-oriented working time flexibility and employees' work-life balance, as well as the moderating role of segmentation preference. We use data from around 18,000 employees from the 2015 Working Time Survey of the Federal Institute for Occupational Safety and Health in Germany. Survey data were collected through computer-assisted telephone interviews. Hierarchical regression analysis revealed that individual-oriented working time flexibility was positively related to employees' work-life balance, whereas organization-oriented working time flexibility had a~negative effect. Employees' individual preferences regarding the segmentation of work and private life only played a~minor role. Those with a~higher segmentation preference profit only marginally more from individual-oriented working time flexibility and suffer only marginally more from organization-oriented working time flexibility demands.Practical Relevance: Taken together, the study's findings highlight the importance of the design of flexible working time arrangements for improving employees' work-life balance. Employers should grant their employees a~certain degree of working time autonomy while keeping organization-oriented working time requirements, such as changes of working time at short notice to accommodate operational demands, to a~minimum. This applies to all employees, not only those with a~strong preference for separating work and private life.
Keywords: 650; Border theory; Segmentation preference; Work-life balance; Working time flexibility; Working time control; Border Theory; Segmentationspräferenz; Work-Life-Balance; Arbeitszeitflexibilität; Arbeitszeitautonomie